Novel flow cytometry analyses of boar sperm viability: Can the addition of whole sperm-rich fraction seminal plasma to frozen-thawed boar sperm affect it? - Torres, Mariana Andrade; Díaz, Rommy; Boguen, Rodrigo; Martins, Simone Maria Massami Kitamura; Ravagnani, Gisele Mouro; Leal, Diego Feitosa; De Lima Oliveira, Melissa; Muro, Bruno Bracco Donatelli; Parra, Beatriz Martins; Meirelles, Flávio Vieira; Papa, Frederico Ozanan [UNESP]; Dell'Aqua, José Antônio [UNESP]; et al. (Public Library of Science (PLoS), 2016)
Boar semen cryopreservation remains a challenge due to the extension of cold shock damage. Thus, many alternatives have emerged to improve the quality of frozen-thawed boar sperm. Although the use of seminal plasma arising from boar sperm-rich fraction (SP-SRF) has shown good efficacy; however, the majority of actual sperm evaluation techniques include a single or dual sperm parameter analysis, which overrates the real sperm viability. Within this context, this work was performed to introduce a sperm flow cytometry fourfold stain technique for simultaneous evaluation of plasma and acrosomal membrane integrity and mitochondrial membrane potential. We then used the sperm flow cytometry fourfold stain technique to study the effect of SP-SRF on frozen-thawed boar sperm and further evaluated the effect of this treatment on sperm movement, tyrosine phosphorylation and fertility rate (FR). The sperm fourfold stain technique is accurate (R2 = 0.9356, p > 0.01) for simultaneous evaluation of plasma and acrosomal membrane integrity and mitochondrial membrane potential (IPIAH cells). Centrifugation pre-cryopreservation was not deleterious (p > 0.05) for any analyzed variables. Addition of SP-SRF after cryopreservation was able to improve total and progressive motility (p < 0.05) when boar semen was cryopreserved without SP-SRF; however, it was not able to decrease tyrosine phosphorylation (p > 0.05) or improve IPIAH cells (p > 0.05). FR was not (p > 0.05) statistically increased by the addition of seminal plasma, though females inseminated with frozen-thawed boar semen plus SP-SRF did perform better than those inseminated with sperm lacking seminal plasma. Thus, we conclude that sperm fourfold stain can be used to simultaneously evaluate plasma and acrosomal membrane integrity and mitochondrial membrane potential, and the addition of SP-SRF at thawed boar semen cryopreserved in absence of SP-SRF improve its total and progressive motility.